Unleashed - Reisz, Kristopher (Simon Pulse, 2008)
Daniel Morning, a handsome, intelligent, and popular teenager, is tired of trying to live up to everyone else's expectations. Then he meets Misty, a rebellious outcast who has mastered the art of shapeshifting. Daniel learns from Misty how to transform himself into a wolf, and he begins to fall in love with the freedom it gives him. But he will soon learn that such freedom comes at a price.